ئاستی بەكارهێنانی ئامڕازەكانی میدیای نوێ لای مامۆستایانی باخچە لەشاری پایـــــە و ئاڵنگارییەکانی پەیوەندییە دەرەکییەکانی هەرێمی کوردستان لێکۆڵینەوەیەک لە جوگرافیای سیاسیدا (توێژینەوەی هەڵێنجراو) - خورشید, فؤاد حمە; صالح, زمناکۆ عثمان (Sulaimani Journal for Humanities, 2023)
This Research discusses the challenges of the Kurdistan Region's external relations as a semi-independent non-government character due to the presence of unchangeable geographical principles and its stand among the unstable geopolitical events that affected its external relations. These factors have changed their effects according to the stages, sometimes causing conflict and sometimes the basis for the development of external relations of the Kurdistan Region. This study aims to identify the most important principles and challenges of the Kurdistan Region's external relations in order to direct the relations in such a way that the problems and pillars are taken into account. Various methods are studied in order to get the result of this study such as methods of (descriptive, analytical and historical) to reveal and introduce the pillars and challenges of external relations of the Kurdistan Region, as it appears that the region is an important geopolitical center and has many geographical factors for the direction and growth of its external relations.
Keywords: International Relations; External Relations; Geographical Principles; Geopolitical Events; Kurdistan Region